TINJAUAN HUKUM MENGENAI SOSIALISASI, EDUKASI DAN INFORMASI TENTANG KEKERASAN SEKSUAL PADA ANAK DI KOTA BANDUNG - Febilita Wulan Sari; Rino Adibowo (Maleo Law Journal, 2017)
Protection of children is a duty and things that should be prioritized in the establishment of a nation and state. As it is known that the child is the future of the nation and state, therefore the obligation of child protection is an absolute must be fulfilled, especially related to the many cases of sexual violence that occur in children today. The obligation is not only in the hands of the central government, but also attached to the local government. Based on that Bandung City Government seeks to fulfill obligations in the protection of children's rights through the establishment of Local Regulation No. 10 of 2012 on the Implementation of Child Protection. The problem is the extent of socialization efforts undertaken by the Government of Bandung on Local Regulation no. 10 Year 2012 on the implementation of child protection related to sexual violence in children and how the synergy of related parties in providing education to the community about child sexual abuse in Bandung and what actions can be done so that information related to child sexual violence can increase child protection in Bandung. The method used is analytical descriptive with normative juridical approach and data collection technique is done through library research and field research through interview. The results of the study found that socialization efforts so far have been done but only recently are global about child protection, not specific related to sexual violence against children. Synergy of related parties has not been optimal by involving the cooperation of higher education institutions. Actions that can be done is by applying various preventive measures such as packaging of child-friendly information media and parent's understanding, as well as the need to implement educational information programs involving the role of parents, children, and teachers.Keywords : Child, Education, Information, Sexcual Violence, Sociszation.